STUDI KASUS: PENGGUNAAN TYPETASTIC DALAM PEMBELAJARAN TIK UNTUK SISWA KELAS 1 SD LABORATORIUM UPI KAMPUS CIBIRU - Dea Azzahra; Nurina Asri Fitriani; Riska Rahmat Kanigara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Learning is an effort to gain knowledge, abilities and skills, by trying new things that have been experienced. Meanwhile, playing is doing something for fun, but it can be an effective way for learning activities. The context of playing is effective because it can increase motivation and interest in learning in students. In the context of 21st century education, digital-based learning is needed that is relevant to the development of the times and supports the needs of digital literacy for students. The use of typetastic shows that technology can be a solution to overcome challenges in learning. The purpose of this study was to describe the use of typetastic, and its positive impact on ICT learning in grade 1 of elementary school. This study uses a qualitative approach with a case study design. Data collection techniques were carried out through observation, interviews, and documentation which were then analyzed descriptively. The results of this study indicate that the use of typetastic shows a positive impact on student learning motivation, and active student involvement in the learning process. By utilizing applications such as typetastic, students can learn independently and progressively, while teachers can monitor student development easily.